PENGARUH KECERDASAN SPIRITUAL DAN KECERDASAN EMOSIONAL TERHADAP KOMPETENSI PEGAWAI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PEGAWAI BIRO HUMAS DAN PROTOKOL SETDA PROVINSI NTB - Safreza, Muhammad Praditina (Master of Management, Mataram University, 2017)
This research examined the effect of spiritual quotient and emotional quotient toward employee competency and organizational citizenship behavior (OCB) of employees of public relations and protocol bureau of West Nusa Tenggara Province. This research is specifically aimed at determining the significance of the effect of spiritual quotient and emotional quotient on employee competency and OCB. The respondents were employees of public relations and protocol bureau of West Nusa Tenggara Province. This research used the path analysis with smartPLS program. The research showed that spiritual quotient and emotional quotient positively and significantly affect employee competency. Spiritual quotient, emotional quotient and employee competency positively and significantly affect the OCB. Spiritual quotient and emotional quotient positively and significantly affect the OCB throught employee competency. Keyword : Spiritual Quotient, Emotional Quotient, Employee Competency, and Organizational Citizenship Behavior (OCB).